Análise do processo de implantação do sistema de gestão estratégica com balanced scorecard: estudo de caso de uma organização educacional particular de educação básica do Rio de Janeiro - Maia, Maria Cristina Queiroz (2006)
This dissertation has the purpose of searching the implantation of the strategical management system that uses the tool of the Balanced Scorecard (BSC) in a private school of basic education in Rio de Janeiro, which aims to reach sustentability and differentiation through a professional and transparent management. The chosen theoretical reference uses as its reference the strategical planning according to the schools analysis and the implementation of the strategy through the use of BSC. It approaches strategical factors that base the management of the educational organization, object of the present study of case. It has the purpose of analyzing what has motivated the stakholders (supporters) to implant it, the process of implantation, the outcomes and the critical factores of sucess of the implantation. As a result, the suggestion of an approach beyond the BSC